Koha 3 library management system install, configure, and maintain your Koha installation with this easy-to-follow guide - Sirohi, Savitra (Packt Pub., 2010)
Annotation
Keywords: Management information systems; Libraries -- Automation; Systèmes d'information de gestion; Bibliothèques; Automatisation; Libraries; Automation